HDC downregulation induced by chronic stress promotes ovarian cancer progression via the IL-6/STAT3/S100A9 pathway - Chen, Zhicong; Cao, Jinming; Xiao, Zhijun; Yang, Zhen; Cheng, Yuanchi; Duan, Jingjing; Zhou, Ting; Xu, Feng (Frontiers in Pharmacology, 2024)
Objective: This study aimed to investigate the underlying mechanism of chronic stress promoting ovarian cancer growth comorbid\ with depression and to evaluate the potential role of histamine (HIS) in treating this comorbidity.: Chronic unpredictable mild stress (CUMS) was used to establish a comorbid mouse model of ovarian cancer and depression. The behavioral phenotypes were assessed using the sucrose preference test (SPT), tail suspension test (TST), forced swimming test (FST), and open field test (OFT). Ovarian cancer growth was monitored by tracking tumor volume and weight. HDC expression in tumor tissue were analyzed using western blot and qRT-PCR techniques. The serum levels of inflammatory factors (IL-6, IL-17A), stress hormones (norepinephrine, NE and cortisol, COR), histamine, and 5-hydroxytryptamine (5-HT) were detected by ELISA.In vitro experiments were conducted to explore the direct impacts of stress hormones on A2780 and ES-2 ovarian cancer cell lines, as well as the modulation of these effects by histamine. HDC knockdown and overexpression approaches were used to study its regulatory role in the IL-6/STAT3/S100A9 signaling pathway.Results: Chronic stress not only induced depressive behaviors but also accelerated ovarian cancer growth in mice by downregulating HDC expression in tumors. While exogenous HIS treatment alleviated depressive symptoms, suppressed cancer growth, and countered the decreased levels of HIS as well as increased levels of IL-6, IL-17A, NE, COR and 5-HT induced by CUMS. Furthermore, HIS positively modulated the immune response by increasing the populations of CD3 + T and CD8 + T cells, and reducing IL-17A secretion. In vitro experiments revealed that stress hormones downregulated HDC, consequently promoting cancer cell proliferation, migration, and invasion via the IL-6/STAT3/S100A9 pathway. Knockdown of HDC activated this pathway, whereas HDC overexpression inhibited its activation.Chronic stress leads to the downregulation of HDC expression thereby facilitating the progression of ovarian cancer progression through the IL-6/STAT3/S100A9 pathway. HIS might serve as a potential molecule for treating the comorbidity of ovarian cancer and depression.